2010
DOI: 10.1038/hdy.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

A locus-wide approach to assessing variation in the avian MHC: the B-locus of the wild turkey

Abstract: Studies of major histocompatibility complex (MHC) diversity in non-model vertebrates typically focus on structure and sequence variation in the antigen-presenting loci: the highly variable and polymorphic class I and class IIB genes. Although these studies provide estimates of the number of genes and alleles/locus, they often overlook variation in functionally related and co-inherited genes important in the immune response. This study utilizes the sequence of the MHC B-locus derived from a commercial turkey to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Recent studies on the major histocompatibility complex (MHC) revealed increased haplotype variability in wild turkey as compared to domestic turkeys [39], [40]. The domestic turkey is recognized as a single breed with eight different varieties defined primarily by plumage color [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the major histocompatibility complex (MHC) revealed increased haplotype variability in wild turkey as compared to domestic turkeys [39], [40]. The domestic turkey is recognized as a single breed with eight different varieties defined primarily by plumage color [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increasing availability of sequence data, it is possible to design primers that amplify target regions and in this issue, Chaves et al (2011) show that singlenucleotide polymorphism haplotyping can be used to capture variation within the MHC-B locus. The authors applied this method to compare MHC diversity of individuals from three different subspecies of wild turkey (Meleagris gallopavo, Figure 1) from the United States with the commercial turkeys.…”
mentioning
confidence: 99%